Proinsulin‐specific T‐cell responses correlate with estimated c‐peptide and predict partial remission duration in type 1 diabetes. Issue 7 (26th July 2021) - Musthaffa, Yassmin; Hamilton‐Williams, Emma E; Nel, Hendrik J; Bergot, Anne‐Sophie; Mehdi, Ahmed M; Harris, Mark; Thomas, Ranjeny
Abstract: Objective: Type 1 diabetes (T1D) is an autoimmune disorder in which autoreactive T cells destroy insulin‐producing β‐cells. Interventions that preserve β‐cell function represent a fundamental therapeutic goal in T1D and biomarkers that predict and monitor β‐cell function, and changes in islet autoantigenic signatures are needed. As proinsulin and neoantigens derived from proinsulin peptides (hybrid insulin peptides, HIPs) are important T1D autoantigens, we analysed peripheral blood CD4 + T‐cell autoantigen‐specific proliferative responses and their relationship to estimated β‐cell function. Methods: We recruited 72 people with and 42 without T1D, including 17 pre‐diabetic islet antibody‐positive and 9 antibody‐negative first‐degree relatives and 16 unrelated healthy controls with T1D‐risk HLA types. We estimated C‐peptide level at 3‐month intervals for 2 years post‐diagnosis and measured CD4 + T‐cell proliferation to proinsulin epitopes and HIPs using an optimised bioassay. Results: We show that CD4 + T‐cell proliferation to any islet peptide and to multiple epitopes were significantly more frequent in pre‐diabetic islet antibody‐positive siblings and participants with T1D ≤ 3 months of duration, than in participants with T1D > 3 months or healthy controls. Among participants with T1D and first‐degree relatives, CD4 + T‐cell proliferation occurred most frequently in response to proinsulin33‐63 (full‐length C‐peptide). Proinsulin33‐63 ‐specific responses were associated with HLA‐DR3‐DQ2 and/or HLA‐DR4/DQ8 . In children with T1D, proinsulin33‐63 ‐specific T‐cell proliferation positively associated with concurrent estimated C‐peptide and predicted survival in honeymoon. Conclusion: CD4 + T‐cell proliferative responses to proinsulin‐containing autoantigens are common before and immediately after diagnosis of T1D but decline thereafter. Proinsulin33‐63 ‐specific CD4 + T‐cell response is a novel marker of estimated residual endogenous β‐cell function and predicts a better 2‐year disease outcome. Abstract : In this study, we found CD4 + T‐cell proliferative responses to proinsulin‐containing autoantigens are common before and immediately after diagnosis of type 1 diabetes but decline thereafter. Proinsulin33‐63 ‐specific CD4 + T‐cell response is a novel marker that correlates with increased estimated endogenous insulin production.